2005
DOI: 10.1248/cpb.53.696
|View full text |Cite
|
Sign up to set email alerts
|

Saponins and Other Constituents from the Leaves of Aralia elata

Abstract: Aralia elata SEEM. (Araliaceae) is widely distributed in the northeast of China and Korea. Its root bark has been used as a folk medicine for tonic, anti-arthritic, and anti-diabetic effect.1) The young shoot of A. elata is a popular edible plant, especially in the spring in Korea and Japan. Many saponins have been isolated from this plant, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and were reported to show anti-diabetic activity, 17) cytoprotective effect on CCl 4 -induced hepatic injury, 7) ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 27 publications
1
2
0
2
Order By: Relevance
“…Similar behavior was observed by Kim et al [42] and Lima. [35] Comparing again the release rate of the liposomes constituted by PCH and PCH þ CHOL, it is observed that the CHOL seems to delay the release of the CAF, since after 12 hours of release, was observed that 57% of the CAF present in the former liposomes constituted by PCH was released, whereas only that 49.64% of the CAF present in liposomes constituted by PCH=CHOL was released.…”
Section: Encapsulation Efficiencysupporting
confidence: 90%
“…Similar behavior was observed by Kim et al [42] and Lima. [35] Comparing again the release rate of the liposomes constituted by PCH and PCH þ CHOL, it is observed that the CHOL seems to delay the release of the CAF, since after 12 hours of release, was observed that 57% of the CAF present in the former liposomes constituted by PCH was released, whereas only that 49.64% of the CAF present in liposomes constituted by PCH=CHOL was released.…”
Section: Encapsulation Efficiencysupporting
confidence: 90%
“…To overcome the above problem, phosphatidyl choline along with non-ionic surfactant is generally used as a component for stabilizing the vesicle membrane of niosomes. In addition, PC acts as skin penetration enhancer and can be expected to facilitate the skin permeation of celecoxib [18].…”
Section: Preparation and Characterizationmentioning
confidence: 99%
“…Many triterpenoid saponins in A. elata have been reported to have hypoglycemic activity and cytoprotective effects on carbon tetrachloride-induced hepatic injury (Kim et al, 2005). The 3-O-monodesmoside structure of oleanolic acid, where C-3 is linked to sugars, has been reported as essential to inhibitory effects on ethanol absorption in rats as well as producing potent hypoglycemic effects in an oral glucose tolerance test in rats (Yoshikawa et al, 1993(Yoshikawa et al, , 1994(Yoshikawa et al, , 1995(Yoshikawa et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%